2022
DOI: 10.1186/s12864-022-08856-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide identification of walnut PP2C family genes in response to external stimulus

Abstract: Walnut is an important economic tree species while confronting with global environmental stress, resulting in decline in quality and yield. Therefore, it is urgent to elucidate the molecular mechanism for the regulation of walnut response to adversity. The protein phosphatase 2C (PP2C) gene family participates in cellular processes in eukaryotes through reversible phosphorylation of proteins and signal transduction regulation. However, the stress response function of PP2C genes was far to be clarified. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…The previous studies showed that the conserved domains in transcription factors (TFs) might be related to gene functions, and the cis -acting elements play roles in the regulation of genes and post-transcriptional modification; similar results have also been found in other plant studies [ 28 , 37 , 39 ]. All CBF proteins contained only one domain, AP2, indicating that they play key roles in plant growth, development, and stress, which is consistent with the previous studies [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The previous studies showed that the conserved domains in transcription factors (TFs) might be related to gene functions, and the cis -acting elements play roles in the regulation of genes and post-transcriptional modification; similar results have also been found in other plant studies [ 28 , 37 , 39 ]. All CBF proteins contained only one domain, AP2, indicating that they play key roles in plant growth, development, and stress, which is consistent with the previous studies [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 71%
“…Cis -acting elements are well-known participants in the control of gene expression [ 37 , 38 , 48 ]. In our study, many cis -acting elements associated with responsiveness to light and phytohormones were identified in the upstream CBF and ICE promoter regions ( Figure 4 ), which suggests that both CBF and ICE proteins might be associated with photosynthetic and hormone responses and regulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After identification of the ramie PP2C gene family, 63 members of the BnPP2C family were mapped on the chromosomes by TBtools and renamed according to the chromosome number and the order of the position of each gene on the chromosome (BnPP2C1-BnPP2C63). The analysis showed that the 62 BnPP2C genes assembled were unevenly distributed on the 14 chromosomes of ramie (Figure 3), with most BnPP2Cs anchored in Chr1 (8). Only two BnPP2Cs in each were anchored in Chr5, Ch10 and Chr12.…”
Section: Chromosome Distribution and Gene Duplication Of Bnpp2csmentioning
confidence: 99%
“…The PP2C families have been reported in many plant species, such as Arabidopsis thaliana (80) [5], wheat (Triticum aestivum) (257) [6], cucumber (Cucumis sativus) (56) [7], walnut (Juglans regia) (44) [8], etc. Phylogenetic analysis classified the 80 AtPP2C genes in Arabidopsis into 13 subfamilies (A-L), while the other seven were not involved in the grouping.…”
Section: Introductionmentioning
confidence: 99%